Influence of Attitude and Entrepreneurial Education on Students’ Intention in Pontianak City - Sin, Sinta alias Jau Fi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Sabda Setia, 2025)
This study explores the influence of attitude and entrepreneurial education on students’ entrepreneurial intention in Pontianak City. The urgency of this topic lies in the need to foster a generation of youth prepared for the digital-based business landscape. Entrepreneurial intention among students is shaped by internal beliefs and educational experiences, both of which are key in forming future entrepreneurs. This research aimed to analyse how attitude and entrepreneurial education affect students’ intention to start a business, and whether entrepreneurial education mediates the relationship between attitude and intention. A quantitative approach was employed, with data collected through an online questionnaire distributed to 133 university students. The data were analysed using multiple regression and mediation analysis. The findings reveal that both attitude and entrepreneurial education significantly influence entrepreneurial intention, with entrepreneurial education playing a dominant role. Moreover, entrepreneurial education acts as a mediating variable, strengthening the relationship between a positive entrepreneurial attitude and intention. This study contributes to the literature by validating the Theory of Planned Behaviour in a local educational context and providing practical insights for curriculum development. The novelty of this study lies in its focus on Pontianak’s student population and the integration of entrepreneurial education as a pathway from mindset to action.